2021
DOI: 10.3389/fnbot.2021.662181
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Optimizing Co-adaptation in Body-Machine Interfaces

Abstract: The operation of a human-machine interface is increasingly often referred to as a two-learners problem, where both the human and the interface independently adapt their behavior based on shared information to improve joint performance over a specific task. Drawing inspiration from the field of body-machine interfaces, we take a different perspective and propose a framework for studying co-adaptation in scenarios where the evolution of the interface is dependent on the users' behavior and that do not require ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…The process involves recording and filtering raw sEMG activity, followed by the selection of relevant features [16]. These selected features are then mapped to low-dimensional control signals, commonly achieved through linear dimensionality reduction (e.g, principal component analysis or non-negative matrix factorization [13, 50]), regression [27, 41], or classification [48, 60]. These mappings in myoelectric interfaces are typically programmed offline, without the user in the loop [13].…”
Section: Related Workmentioning
confidence: 99%
“…The process involves recording and filtering raw sEMG activity, followed by the selection of relevant features [16]. These selected features are then mapped to low-dimensional control signals, commonly achieved through linear dimensionality reduction (e.g, principal component analysis or non-negative matrix factorization [13, 50]), regression [27, 41], or classification [48, 60]. These mappings in myoelectric interfaces are typically programmed offline, without the user in the loop [13].…”
Section: Related Workmentioning
confidence: 99%
“…A classic approach to designing a BoMI map is to describe a linear relationship between sensor measurements and robot control commands [6]. More recent examples use iterative linear methods [14], feedback control (as opposed to feedforward control) [15], and deep learning methods such as adaptive nonlinear autoencoders [16].…”
Section: Related Workmentioning
confidence: 99%
“…Previous experiments have shown that tree-based models such as Random Forests seem to perform well in a supervised multimodal HMI for activity recognition [24]. Additional factors such as a co-adaptive environment can further enhance HMI performance [30,31]. Hereby, human and machine interact through closed feedback loops in a mutual learning environment.…”
Section: Introductionmentioning
confidence: 99%
“…The user receives constant feedback based on his actions, while the machine receives new training samples over time and adapts to the human. This can potentially stabilize HMI performance by mitigating non-stationary properties and helps compensate for effects over time, such as fatigue and sensor signal degradation [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%